Association of characteristics of farmers with adoption of improved chickpea production technology - Chaudhary, R.P.; Singh, A.K.; Singh, S.K.; Goyal, V.; Singh, I.P. (Annals of Agricultural Research, 2014)
India is the largest producer of chickpea in the world accounting for 67% of global production. Chickpea is grown on about 7.29 million ha area with annual production of 5.77 MT grain which represent 30% and 38% of pulses acreage and production in India. Its production has gone up from 3.65 to 5.77 MT between 1950-51 to 2003-04 registering an annual growth rate of 0.58%, which is far less than the population growth causing a wide gap in the demand and supply of chickpea. The major chickpea growing states are Madhya Pradesh, Rajasthan, Uttar Pradesh, Maharashtra, Andhra Pradesh, Gujarat and Karnataka. Chickpea productivity in the country is almost static (750-800 kg/ ha) mainly due to poor adoption of improved varieties and scientific production techniques by the farmers. The investigation was carried out in Bhagyanagar block of Auraiya district (U.P.) in the year 2008-09. A total of 80 farmers were selected from two villages namely Kuthra & Parghaipur through proportionately random sampling technique. The data were collected from the respondentswith the help of a well structured interview schedule. The correlation was computed to know the relation of characteristics of respondents with their extent of adoption of recommended cultivation practices of chickpea. It was concluded that the characteristics namely education, size of farm holding, knowledge, social participation and socio-economic status had a positive and significant relationship with adoption whereas farming experience and risk orientation were found nonsignificant with level of adoption of chickpea. Hence, keeping these variables in mind, farmers will have to be trained properly about improved production technology of chickpea that would beable to educate and transfer the technology more electively among the chickpea growers.